Hubungan Self-Efficacy dengan Academic Resilience Dimediasi Self-Regulated Learning pada Mahasiswa di Masa Pandemi COVID-19 - Yoelianita, Betty Erda; Toga, Ervia (Holistic Nursing and Health Science, 2022)
Introduction: The COVID-19 pandemic had affected of higher education, especially nursing students in online clinical practice learning. The impact of online learning was students difficulties and limitations in direct clinical learning. A significant decrease in the statistical value of nursing practice pre-pandemic and during the pandemic in this situation, students with adaptive responses through their capacity used self-regulated learning (SRL) and academic resilience strategies. This study aimed to examine the role of SRL as a mediator of the correlation between self-efficacy and academic resilience at bachelor of nursing students during the Covid-19 pandemic. Methods: This study used a quantitative approach with a cross-sectional study design. The research sample consisted of 138 bachelor of nursing students at a health institution in East Java, taken using purposive sampling techniques. The inclusion criteria were bachelor of nursing students, who had practiced clinial at hospitals or other practice areas, during the Covid-19 pandemic. The research instrument used self-efficacy scale (17 items), academic resilience scale (25 items), and SRL scale (39 items). Data analysis used analyze regression Process Hayes Version 4.0 with the IBM SPSS (Statistical Program for Social Science) version 25 program for windows. Results: The results showed that there was a positive and significant correlation between self-efficacy and academic resilience, either directly (β=1.396, p=0.000) or partially mediated by SRL (β=0.7126, p=0.000), which mean that students with high self-efficacy can increase academic resilience with the mediating role of SRL.Conclusion: Self-efficacy has a positive and significant effect on academic resilience, either directly or partially mediated by SRL.  Keywords: Academic Resilience, Self-Efficacy, Self-Regulated Learning.